Communication restriction in adults who stutter: Part III. (1st November 2016) - Lee, Amanda Savio; Robb, Michael; Van Dulm, Ondene; Ormond, Tika
ABSTRACT: This is the third article in a series examining communication restriction in adults with stuttering (AWS). The aim was to explore interpersonal communication behaviour in AWS at long-term treatment follow-up, using systemic functional linguistics (SFL) as an analytical framework. The performance of 10 AWS within 10-minute conversation samples was compared across pretreatment (T1), post-treatment (T2), and 12-month follow-up (T3), in terms of language productivity and complexity, modality, and appraisal. At T1 and T3, comparisons were also made to a control group (AWNS). Post-treatment increases in (1) language complexity, (2) frequency of modal operators, and (3) expression of appraisal were maintained in the AWS group at T3. No significant differences in these areas were found between AWS and AWNS at T3. The findings suggest that intensive comprehensive stuttering treatment can affect lasting functional change in interpersonal language use for AWS.